2006
DOI: 10.1111/j.1439-0507.2006.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibilities of Malaysian clinical isolates of Cryptococcus neoformans var. grubii and Cryptococcus gattii to five antifungal drugs

Abstract: The in vitro susceptibilities of Malaysian clinical isolates of Cryptococcus neoformans var. grubii and C . gattii to five antifungal drugs (amphotericin B, flucytosine, fluconazole, itraconazole and ketoconazole) were determined using the Etest method. None of the Malaysian isolates was resistant to amphotericin B and ketoconazole. Isolates resistant to flucytosine, fluconazole and itraconazole were observed in this study. Minimum inhibition concentrations (MICs) of > or = 32 microg ml(-1) against flucytosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
6
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
6
15
6
1
Order By: Relevance
“…This species has long been noted to be an important opportunistic pathogen in tropical and subtropical climates and has recently gained importance due to an outbreak of C. gattii on Vancouver Island, BC, Canada (10,15,39). The decreased susceptibility of this species of Cryptococcus to fluconazole is similar to that observed by other investigators (14,42,43), although a recent report from Africa found low MICs to fluconazole and other azoles (15). Both C. gattii and C. neoformans were very susceptible to voriconazole in the present study (Table 9).…”
Section: Vol 45 2007 Global Susceptibility Of Yeasts To Antifungal supporting
confidence: 77%
“…This species has long been noted to be an important opportunistic pathogen in tropical and subtropical climates and has recently gained importance due to an outbreak of C. gattii on Vancouver Island, BC, Canada (10,15,39). The decreased susceptibility of this species of Cryptococcus to fluconazole is similar to that observed by other investigators (14,42,43), although a recent report from Africa found low MICs to fluconazole and other azoles (15). Both C. gattii and C. neoformans were very susceptible to voriconazole in the present study (Table 9).…”
Section: Vol 45 2007 Global Susceptibility Of Yeasts To Antifungal supporting
confidence: 77%
“…grubii, which agrees with several previous reports (Fernandes et al, 2003;Trilles et al, 2004;Khan et al, 2007Khan et al, , 2009Gomez-Lopez et al, 2008). However, there is divergence of results concerning the antifungal susceptibility patterns of the two species in some other studies, which reported no such difference (Chen et al, 2000;Calvo et al, 2001;Morgan et al, 2006;Tay et al, 2006;Thompson et al, 2009). This divergence in results may be due to a possible lack of uniformity in the methodologies of testing adopted by different investigators.…”
Section: Discussionsupporting
confidence: 53%
“…Studies conducted in several parts of the world have shown low MIC 50 and MIC 90 values for fluconazole against C. neoformans VNI [43][44][45]. In this study, the MIC 50 and MIC 90 values for fluconazole were 4-8 mg/L; however, higher values (2-128 mg/L) have been reported for isolates of C. neoformans VNI [46].…”
Section: Discussioncontrasting
confidence: 43%
“…High MIC values (≥ 64 mg/L) have been reported for fluconazole against C. gattii [44,47], in contrast to this study, which determined values ≤ 16 mg/L. Hagen et al [48] analyzed 350 isolates of C. gattii originating from clinical, environmental and animal sources and reported that MIC values for flucytosine and fluconazole were higher, i.e.…”
Section: Discussioncontrasting
confidence: 40%